2009
DOI: 10.5038/2375-0901.12.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Transit Response to Congestion Pricing Opportunities: Policy and Practice in the U.S.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The most extensive treatment considers only a quarter of current facilities (Turnbull 2008). Given concerns that transit agencies are not optimizing the opportunity afforded by such congestion pricing (Hardy 2009), there is a need to comprehensively examine and assess the integration of transit with HOT lanes in the United States. This research is a response to that need.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensive treatment considers only a quarter of current facilities (Turnbull 2008). Given concerns that transit agencies are not optimizing the opportunity afforded by such congestion pricing (Hardy 2009), there is a need to comprehensively examine and assess the integration of transit with HOT lanes in the United States. This research is a response to that need.…”
Section: Discussionmentioning
confidence: 99%
“…The model predicted that very few bus riders would shift to driving alone in the HOT lane (6). However as late as 2009, Hardy reported that there was still an overall lack of formal evaluation in this area (7).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model predicted that very few bus riders would shift to driving alone in the HOT lane (3). However, as late as 2009, Matthew Hardy reported in the Journal of Public Transportation that there was still an overall lack of formal evaluation in this area (4).…”
Section: Literature Reviewmentioning
confidence: 99%